Development of a method for rapid evaluation of the color of flour and pasta made from wheat of different species - Л. А. Вечерська; О. В. Голік; Л. І. Реліна; Л. І. Буряк; Т. А. Шелякіна (Plant Varieties Studying and Protection)
Purpose. Develop a simplified method for estimating the color of flour and pasta using Adobe Photo Shop® software.